Challenges of virtual university education in Lima: Qualitative analysis in the context of COVID-19. - Figueroa Rojas, Jose Jesus (2021)
of COVID-19, the main challenges and inconveniences in its application, the benefits that this modality brings to higher education, the skills and tools necessary for its development. and the probability of success according to the capacities of the population. For its development, a qualitative approach and search tools such as Scopus, Scielo, Latindex and Google Scholar were used, as a result of the analysis it was possible to determine that the impact of the incorporation of these tools provides challenges, using a combination of ICT platforms and tools Videoconferencing offers an alternative in higher education in times of pandemic, without dependence on space, it will allow the development of learning sessions without losing the essence of face-to-face sessions and without offering disadvantages due to the technological gap since the percentages of access to ICTs are they have increased over the years to reach 98% access by Peruvian households. In conclusion, virtual education is the timely selection in the university sector to present a complete and quality teaching process in times of COVID-19.